An efficient method to determine double Gaussian fluence parameters in the eclipse™ proton pencil beam model. Issue 12 (15th November 2016) - Shen, Jiajian; Liu, Wei; Stoker, Joshua; Ding, Xiaoning; Anand, Aman; Hu, Yanle; Herman, Michael G.; Bues, Martin
Abstract : Purpose: To find an efficient method to configure the proton fluence for a commercial proton pencil beam scanning (PBS) treatment planning system (TPS). Methods: An in‐water dose kernel was developed to mimic the dose kernel of the pencil beam convolution superposition algorithm, which is part of the commercial proton beam therapy planning software, eclipse ™ (Varian Medical Systems, Palo Alto, CA). The field size factor (FSF) was calculated based on the spot profile reconstructed by the in‐house dose kernel. The workflow of using FSFs to find the desirable proton fluence is presented. The in‐house derived spot profile and FSF were validated by a direct comparison with those calculated by theeclipse TPS. The validation included 420 comparisons of the FSFs from 14 proton energies, various field sizes from 2 to 20 cm and various depths from 20% to 80% of proton range. Results: The relative in‐water lateral profiles between the in‐house calculation and theeclipse TPS agree very well even at the level of 10 −4 . The FSFs between the in‐house calculation and theeclipse TPS also agree well. The maximum deviation is within 0.5%, and the standard deviation is less than 0.1%. Conclusions: The authors' method significantly reduced the time to find the desirable proton fluences of the clinical energies. The method is extensively validated and can be applied to any proton centers using PBS and theeclipse TPS.